Epidemiology, Regional Characteristics, Knowledge, and Attitude Toward Female Genital Mutilation/Cutting in Southern Iran. (1st July 2015) - Dehghankhalili, Maryam; Fallahi, Soghra; Mahmudi, Forugh; Ghaffarpasand, Fariborz; Shahrzad, Mohammad Esmaeil; Taghavi, Mohsen; Fereydooni Asl, Marjan
ABSTRACT: Introduction: Female genital mutilation/cutting (FGM/C), also known as female circumcision, is an ancient traditional procedure that involves partial or total removal of the female external genitalia for nonmedical reasons. Although it is well described in African and some Arabic countries, data from Iran are scarce. Aim: To describe the epidemiology, regional characteristics, knowledge, and attitude toward FGM/C in Southern Iran. Methods: This cross‐sectional study was conducted during a 36‐month period from 2010 to 2013 in Hormozgan, a southern province of Iran near the Persian Gulf. We included 780 women in six major rural areas of the province who referred to healthcare centers for vaccination, midwifery, or family planning services. All participants underwent complete pelvic examination to determine the type of FGM. The questionnaire consisted of several sections such as demographic and baseline characteristics, and two self‐report sections addressing the knowledge and attitude toward FGM/C and its complications. Baseline sociodemographic characteristics including age, educational level, marital status, religion, and nationality were the independent variables. Results: Among the participants, 535 (68.5%) had undergone FGM/C. FGM/C was associated with higher age ( P  = 0.002), Afghan nationality ( P  = 0.003), Sunni Islam as religion ( P  = 0.019), illiteracy ( P  < 0.001), and family history of FGM/C in mother ( P  < 0.001), sister ( P  < 0.001), and grandmother ( P  < 0.001). Ancient traditions in the area (57.1%) were mentioned as the most important factor leading to FMG/C. Urinary tract infection was the most common reported complication (60.4%). Conclusion: FGM/C is a common practice in rural areas of Southern Iran. It is associated with increased age, illiteracy, Sunni Islam religion, Afghan nationality, and positive family history. Lack of knowledge toward FGM/C is the main cause of its high prevalence and continuation in the area.